Performance of Dry Direct Seeded Rice and Weeds on Sesbania Brown Manuring as Compared to Farmers’ Practice and Chemical Control Method - Chaudhary, Sunil Kumar; Marahatta, Santosh; Chaudhary, Manisha (International Journal of Applied Sciences and Biotechnology, 2018)
The research was conducted to study the comparison of farmers’ weed management practice in rice with chemical control and Sesbania co-culture. The experiment was laid out in Randomized Complete Block Design (RCBD) with three replications and five different weed management practices. The five treatments were Farmers’ practice (two hand weeding first at 28 DAS and another at 40 DAS), Chemical practice (Bispyribac sodium as post emergence @ 25 g a.i. ha-1 at 25 DAS), Sesbania co-culture (100 kg Sesbania ha-1 and knocking down at 28 DAS), Weed free (Hand removal of weeds at 10 days’ interval) and Weedy check (No weed management). The individual plot size was 5 x 4 m2. The Sesbania co-culture and farmers’ practice were found more or less similar performance for all observed parameters but as better as compared to weedy check and chemical treatment. Sesbania co-culture was found less costly than farmers’ practice for weed management. The experiment clearly demonstrated the importance of brown manuring on effective control of weeds in rice field under dry direct seeded rice. Int. J. Appl. Sci. Biotechnol. Vol 6(3): 265-269